ANALYSIS OF THE EFFECT OF FINANCIAL PERFORMANCE AND WORKING CAPITAL MANAGEMENT ON STOCK RETURN AT PT BANK DANAMON INDONESIA TBK - Sullissetiawati, Sullissetiawati; Munandar, Aris (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
This study aims to determine whether there is a significant effect of financial performance and working capital management on Stock Returns at PT Bank Danamon Indonesia, Tbk partially or simultaneously. This type of research is associative research, with quantitative data from secondary data. The population in this study is the data on the Financial Position Report, Profit and Loss, Notes on Financial Statements and Stock Returns for 29 years, from 1989-2018. The sample in this study is data on Financial Position Reports, Profit and Loss, Notes on Financial Statements and Stock Returns for 7 years, from 2012-2018. The sampling technique used is purposive sampling. Data collection uses documentation and pustakao studies. The data analysis method used is the classical assumption test, multiple linear regression, multiple correlation, determination test, t test and f test. The results of data analysis show that both partially and simultaneously financial performance and working capital management do not significantly influence the Stock Return at PT Bank Danamon Indonesia, Tbk.